Comparing the use and timing of palliative care services in COPD and lung cancer: a population-based survey. Issue 5 (24th May 2018) - Scheerens, Charlotte; Beernaert, Kim; Pype, Peter; Cohen, Joachim; Deliens, Luc; Chambaere, Kenneth
Palliative care is a proven approach to enhance quality of life and care both for people with severe chronic obstructive pulmonary disease (COPD) [1] and those with lung cancer [2], and it is encouraged to start palliative care early in the disease trajectory [3, 4]. Similar symptoms occur in both diseases, such as pain, insomnia, fatigue, low mood and dyspnoea [5], with a study reporting even worse physical and emotional functioning for COPD than for lung cancer [6]. These symptoms signal palliative care needs [6], and require treatment focused on symptom management and psychosocial support for more than just the terminal phase. A high use of healthcare resources in COPD is found, related to a tendency towards aggressive and life-prolonging care [7]. Difficulties in predicting disease trajectories and unclear prognosis have been suggested as explanations for why people with COPD are referred less often for palliative care [8]. Palliative care services are used mainly as terminal care in lung cancer and COPD, with less and later use for COPD http://ow.ly/j38v30jxbhv